(untitled) (Педагогіка вищої та середньої школи, 2004)
The pedagogical model of the process of formation of a specialist, trained at the College of Medicine, includes purposeful, systematic, specially organized interrelation between the subjects of the education, the society and personality, the individual and the social communities.